Cytokines levels in saliva in periodontitis, oral potentially malignant disorders and squamous cell carcinoma - Angel Adamov; Teodora Bolyarova-Konova; Pavel Stanimirov; Evgeniy Aleksiev; Snezhina Mihailova Kandilarova; Marina Miteva; Petya Yankova; Nikolay Ishkitiev; Zornitsa Mihaylova (Biotechnology & Biotechnological Equipment)
Biopsy and histopathological examination continue to be the gold standards for diagnosing oral cancer and oral potentially malignant disorders (OPMD). The prognosis of these conditions is significantly influenced by established factors such as the degree of dysplasia, tumour size, grade, and patient age. While these traditional diagnostic approaches are crucial, there is a growing need for innovative methods to improve diagnosis and monitoring of these conditions. We hypothesize that identifying specific diagnostic biomarkers in human saliva, alongside traditional methods, could enhance clinical outcomes in managing both malignant and non-malignant oral pathologies. In this study, salivary levels of previously described biomarkers BDNF, IL-6, IL-8, IL-10, IL-15, IL-1RA, LIF, and TNF-α were compared among oral cancer patients, patients with OPMD, periodontal disease patients, and healthy volunteers. The results indicated that these cytokines have the potential to distinguish cancer cases, though they are less effective in differentiating between OPMD and periodontitis. Using pairs or groups of biomolecules could improve the ability to differentiate between different pathological entities. We found the following panel IL-6, IL-15, and IL-1RA to be particularly significant as diagnostic biomarkers for oral squamous cell carcinoma and OPMD.